Role of sulfide anion in the development of chronic alcoholic hepatitis under the conditions of modulation of adenosine monophosphate kinase – a correlational study - Mykytenko, Andrii; Akimov, Oleh; Shevchenko, Oleksandr; Neporada, Karine (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Hydrogen sulfide (H 2 S) has attracted the attention of researchers as a novel signaling molecule that affects vascular metabolism, immune function, stress and inflammation. It plays an important role in pathophysiological disorders under the conditions of the development of obesity, diabetes, non-alcoholic fatty liver disease and cardiovascular diseases. The purpose of this work is to establish correlation ratios of H 2 S concentration with markers of oxidative-nitrosative stress and extracellular matrix metabolism of the liver during chronic alcoholic hepatitis modeling and AMPK modulation by phenformin and doxorubicin. Material and methods. The experiments were performed on 36 white, sexually mature male Wistar rats, weighing 180-220 g. Alcoholic hepatitis was modelled by alcohol administration, on the background of alcoholic hepatitis animals received phenformin orally at a dose of 10 mg/kg or doxorubicin at a dose of 1.25 mg/kg intraperitoneally. Statistical processing of the results of biochemical studies was carried out using the non-parametric method of Spearman to determine correlations. Results. H 2 S during alcoholic hepatitis inversely proportionally strongly correlates with the concentration of nitrites, oxyproline and arginase activity. Phenformin administration during alcoholic hepatitis leads to formation of inversely proportionally strongly correlation of H 2 S with the production of superoxide anion radical, the concentration of malondialdehyde, activities of constitutive NO-synthases, nitrite reductases, nitrate reductases, and arginase. Doxorubicin administration during alcoholic hepatitis leads to formation of directly proportional strongly correlation of H 2 S with the activity of constitutive NO-synthases, nitrite reductases, nitrate reductases. Conclusion. Administration of phenformin or doxorubicin expands correlations between H 2 S and indicators of oxidative-nitrosative stress.
Research was conducted in accordance with the standards of the Council of Europe Convention on Bioethics “European Convention for the Protection of Vertebrate Animals Used for Experimental and Other Scientific Purposes” (1997), general ethical principles of experiments on animals approved by the First National Congress on Bioethics of Ukraine (September 2001) and other international agreements and national legislation in this area. Research was approved by Ethical Committee of Poltava State Medical University.
Keywords: AMPK; chronic alcohol hepatitis; doxorubicin; liver; phenformin; sulfide anion